Exosomes in Cerebral Ischemia-Reperfusion Injury: Current Perspectives and Future Challenges - Chao Zhou; Fating Zhou; Yarong He; Yan Liu; Yu Cao (Brain Sciences, 2022)
Cerebral ischemia impedes the functional or metabolic demands of the central nervous system (CNS), which subsequently leads to irreversible brain damage. While recanalization of blocked vessels recovers cerebral blood flow, it can also aggravate brain injury, termed as ischemia/reperfusion (I/R) injury. Exosomes, nanometric membrane vesicles, attracted wide attention as carriers of biological macromolecules. In the brain, exosomes can be secreted by almost all types of cells, and their contents can be altered during the pathological and clinical processes of cerebral I/R injury. Herein, we will review the current literature on the possible role of cargos derived from exosomes and exosomes-mediated intercellular communication in cerebral I/R injury. The PubMed and Web of Science databases were searched through January 2015. The studies published in English were identified using search terms including “exosomes”, “cerebral ischemia-reperfusion injury”, “brain ischemia-reperfusion injury”, and “stroke”. We will also focus on the potential therapeutic effects of stem cell-derived exosomes and underlying mechanisms in cerebral I/R injury. Meanwhile, with the advantages of low immunogenicity and cytotoxicity, high bioavailability, and the capacity to pass through the blood–brain barrier, exosomes also attract more attention as therapeutic modalities for the treatment of cerebral I/R injury.